1993
DOI: 10.1029/92jc03017
|View full text |Cite
|
Sign up to set email alerts
|

The δ18O of dissolved O2 in the surface waters of the subarctic Pacific: A tracer of biological productivity

Abstract: The 18O/16O of dissolved oxygen was measured in the upper ocean of the subarctic Pacific in 1988. In May and August, at stations Papa (50°N, 145°W) and R (53°N, 145°W), the mean δ18O in the mixed layer was 23.84±0.20 and 24.00±0.24 ‰ (versus standard mean ocean water) consistently more depleted than atmospheric saturation levels by about 0.4 ‰. This relative depletion is caused by input of photosynthetically produced O2. A value for the isotopic fractionation effect during respiration (αT) of 0.978±0.006 was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(110 citation statements)
references
References 25 publications
(10 reference statements)
5
103
2
Order By: Relevance
“…Openness of the system-Previous studies have demonstrated that open-system aspects and diffusion have a firstorder influence on the distribution of isotope tracers in the ocean or other aquatic environments (Bender 1990;Quay et al 1993;Lehmann et al 2003). The suitability of the Rayleigh approach to calculating e O-app (i.e., the basis for the estimation of R WC : R Sed ) depends on rates of O 2 replenishment by O 2 production through photosynthesis or vertical mixing.…”
Section: Discussionmentioning
confidence: 99%
“…Openness of the system-Previous studies have demonstrated that open-system aspects and diffusion have a firstorder influence on the distribution of isotope tracers in the ocean or other aquatic environments (Bender 1990;Quay et al 1993;Lehmann et al 2003). The suitability of the Rayleigh approach to calculating e O-app (i.e., the basis for the estimation of R WC : R Sed ) depends on rates of O 2 replenishment by O 2 production through photosynthesis or vertical mixing.…”
Section: Discussionmentioning
confidence: 99%
“…For the respiration fractionation 18 ε R , a large range from −6 ‰ for fish and human respiration to −24 ‰ for the alternative respiratory pathway (AOX) has been reported Helman et al, 2005). For the purposes of the present study, I use 18 ε R = (−20 ± 4) ‰, which is more representative of values reported for marine communities: (−22 ± 3) ‰ in the Southern Ocean (Hendricks et al, 2004), (−21 ± 2) ‰ in the Equatorial Pacific (Hendricks et al, 2005), (−22 ± 6) ‰ in the subarctic Pacific (Quay et al, 1993) and (−20 ± 3) ‰ for different marine organisms (Kiddon et al, 1993). .…”
Section: Respirationmentioning
confidence: 99%
“…dc /dt = 0, is not required. Most parameters (ε E , ε I , δ P ) and variables (s, δ) can be measured with sufficient precision to calculate g. However, ε R is often not sufficiently well-constrained to give precise results for g (Quay et al, 1993). Moreover, f has to be estimated from s and g via f = s/g (Hendricks et al, 2004), which can introduce additional uncertainties, because the relationship f = s/g is derived from assuming dc/dt = 0 and therefore P -R = sν mix c sat , cf.…”
Section: Production Within the Mixed Layermentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, θ R can only be computed if 18 ε R is also known. Even though the influence of the uncertainty in 18 ε R is not as severe as when 18 δ were used for the calculation directly (Quay et al, 1993), this goes against the rationale behind the triple oxygen isotope technique (i.e., the absence of the need to know 18 ε R ). Finally, the suggested approximations are mathematically inconsistent with Eqs.…”
Section: Approximate Calculation Of Gmentioning
confidence: 88%